Detecting Java Code Problem in Accessing Different DBMS for Increasing Easy of Application Migration - Setiawan, Dimas Ari; Adilah, Imamah; Fatchurrochman, Fatchurrochman (Proceedings of the International Conference on Green Technology, 2017)
Any change in the organizational environment causes the need for system migration. Migration in the world of information technology is the process of moving from one system environment to another better system, in an organization. Migration can be done at the database level. Problems arise when the application can not run properly when DBMS changes occur. It is necessary to identify the program code that causes problems so that when the migration is done the application can still run well. In this paper we will identify some problems with the Java program code that causes the migration process to run smoothly and solutions to solve the problem. The study was conducted on Generation Application Schedule Lecture version 1.0 using DBMS Access, MySql, and SqlLite. The result of this research is the common Java program code to access the DBMS. For software developers the results of this study are expected to accelerate the process of system migration.